Prolonged monsoon droughts and links to Indo-Pacific warm pool: A Holocene record from Lonar Lake, central India - Prasad, Sushma; Anoop, A.; Riedel, N.; Sarkar, S.; Menzel, P.; Basavaiah, N.; Krishnan, R.; Fuller, D.; Plessen, B.; Gaye, B.; Röhl, U.; Wilkes, H.; et al. (My University, 2014)
Concerns about the regional impact of global climate change in a warming scenario have highlighted the gaps in our understanding of the Indian Summer Monsoon (ISM, also referred to as the Indian Ocean summer monsoon) and the absence of long term palaeoclimate data from the central Indian core monsoon zone (CMZ). Here we present the first high resolution, well-dated, multiproxy reconstruction of Holocene palaeoclimate from a 10 m long sediment core raised from the Lonar Lake in central India. We show that while the early Holocene onset of intensified monsoon in the CMZ is similar to that reported from other ISM records, the Lonar data shows two prolonged droughts (PD, multidecadal to centennial periods of weaker monsoon) between 4.6–3.9 and 2–0.6 cal ka. A comparison of our record with available data from other ISM influenced sites shows that the impact of these PD was observed in varying degrees throughout the ISM realm and coincides with intervals of higher solar irradiance. We demonstrate that (i) the regional warming in the Indo-Pacific Warm Pool (IPWP) plays an important role in causing ISM PD through changes in meridional overturning circulation and position of the anomalous Walker cell; (ii) the long term influence of conditions like El Niño-Southern Oscillation (ENSO) on the ISM began only ca. 2 cal ka BP and is coincident with the warming of the southern IPWP; (iii) the first settlements in central India coincided with the onset of the first PD and agricultural populations flourished between the two PD, highlighting the significance of natural climate variability and PD as major environmental factors affecting human settlements.
Keywords: Indian summer monsoon; ENSO; Prolonged droughts; Holocene; Lonar Lake; El Niño-Southern Oscillation (ENSO)